Analysis of Sustainability Variables in Revegetation of Ex-Oil and Gas Mining Operation - Abdillah Lbs; Suwondo Suwondo; Nurhasanah Nurhasanah; Nurhayati Nurhayati; Anita Pramawanti (School of Postgraduate Studies, Diponegoro Univer, 2024)
Revegetation after petroleum mining operations is a complex and multifaceted issue that requires careful consideration of sustainability factors to ensure long-term success. PT Pertamina Hulu Rokan has taken its environmental responsibilities seriously and has restored ex-mining land through replanting efforts at ex-well sites, ex-production facilities, and ex-borrow pits. This is important for environmental sustainability, especially after mining oil and gas. This study aims to identify important variables in maintaining the sustainability of revegetation activities at PT Pertamina Hulu Rokan by describing the intensity of influence and interdependence between variables and grouping them from the most influential to the least influential. Focus group discussions (FGDs) were used to collect data, and the MICMAC approach was used to analyze the relationships between variables. This research has identified 13 ecological, socioeconomic, and conflict mitigation variables that are important in land revegetation activities. Based on the results, the relationships between these variables have been derived by highlighting the key indicators that trigger sustainable revegetation efforts, namely variables such as envreg, amdal, local business development (lbd), and relationship. The lbd variable strongly influences the welfare variable, amdal, and the other variables strongly influence the company's image. Post-mining land revegetation efforts at PT Pertamina Hulu Rokan demonstrate the company's commitment to environmental sustainability. By considering sustainability variables in the revegetation process after petroleum mining operations, PT PHR ensures that its rehabilitation efforts can restore land while promoting sustainable practices and providing benefits to local communities.